736 Endoscopic-Guided Decompression of an Incidental, Massive, Infected Fronto-Ethmoidal Mucocele: Our Experience. (19th August 2022) - Muhammad, U; DeCarpentier, J; Noon, E
Abstract: A 55-year-old man was referred to neurology with worsening headaches and right-hand numbness. An MRI brain demonstrated a hemangioblastoma but also a large right sided frontoethmoidal mucocele. The only sino-nasal symptom the patient had was unilateral nasal obstruction but felt this was well-controlled with a steroid nasal spray prescribed in primary care. Nasendoscopy showed pus emanating from a smooth mass anterior in the nasal cavity. A CT scan showed features of a large, expansile mass extending across both frontal and ethmoid sinuses, lateralising the septum, with dehiscence of the lamina papyracea. The patient underwent image-guided endoscopic sinus surgery to drain the mucocele which was filled with a considerable amount of pus and was seen to have eroded all sinus lamellae. Sinonasal mucoceles are expansile collections of mucous, lined with epithelium, and are thought to be more common in the third and fourth decades (1). They are usually caused by sinus surgery as a result of an obstructed sinuses but can follow trauma, inflammation or occur spontaneously (2). Once identified, surgery is the standard of care to prevent complications from expansion or infection. In this case report, along with imaging and intraoperative photographs, we further describe our approach and experience in managing a large mucocele.